2016
DOI: 10.1128/msphere.00038-15
|View full text |Cite
|
Sign up to set email alerts
|

The Dysferlin Domain-Only Protein, Spo73, Is Required for Prospore Membrane Extension in Saccharomyces cerevisiae

Abstract: Prospore membrane formation consists of de novo double-membrane formation, which occurs during the developmental process of sporulation in Saccharomyces cerevisiae. Membranes are formed into their proper size and shape, and thus, prospore membrane formation has been studied as a general model of membrane formation. We identified SPO73, previously shown to be required for spore wall formation, as an additional gene involved in prospore membrane extension. Genetic and cell biological analyses suggested that Spo7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…Prospore membrane closure is partially defective in spo73 ∆, spo71 ∆, and vps13 ∆ cells; in contrast, prospore membrane closure is normal in gip1 ∆ cells ( Park and Neiman, 2012 ). While nuclear capture by the prospore membrane is partially defective in spo73 ∆, spo71 ∆, and vps13 ∆ cells ( Okumura et al , 2016 ), our observations showed that nuclear capture is normal in gip1 ∆ cells.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…Prospore membrane closure is partially defective in spo73 ∆, spo71 ∆, and vps13 ∆ cells; in contrast, prospore membrane closure is normal in gip1 ∆ cells ( Park and Neiman, 2012 ). While nuclear capture by the prospore membrane is partially defective in spo73 ∆, spo71 ∆, and vps13 ∆ cells ( Okumura et al , 2016 ), our observations showed that nuclear capture is normal in gip1 ∆ cells.…”
Section: Resultsmentioning
confidence: 49%
“…However, phenotypes of these mutants are distinct in some regards. While intraluminal vesicles are observed between inner and outer leaflets of the prospore membrane in spo73 ∆, spo71 ∆, and vps13 ∆ cells ( Park and Neiman, 2012 ; Park et al , 2013 ; Okumura et al , 2016 ), no such structures were observed in gip1 ∆ cells ( Tachikawa et al , 2001 ). Prospore membrane closure is partially defective in spo73 ∆, spo71 ∆, and vps13 ∆ cells; in contrast, prospore membrane closure is normal in gip1 ∆ cells ( Park and Neiman, 2012 ).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations